The becoming of the archaeological education at the faculty of history of the Belarusian State University in 1934–1941 - Vaitovich, Aliaksandra V. (Journal of the Belarusian State University. History, 2019)
The article deals with the little-known pages of the history of archaeology and education. It reveals the main aspects of the teaching of archaeology and other disciplines of the relevant profile at the faculty of history of the BSU in 1934–1941. Using the archive sources, the materials of the periodicals and the memoirs of R. A. Nikolskaya, the author traces the most important stages of the becoming of the archaeological education at the BSU. The paper shows that the initial curricula of the faculty included several archaeological courses. Nevertheless, during the pre-war period the students studied only history of the pre-class society and archaeology. The article presents the main achievements of the teaching staff and the peculiarities of the learning process.